IN DEFENSE OF A FEMINIST PSYCHOLOGY: THE CONSTRUCTION OF EMANCIPATORY THEORY AND PRACTICES - Rodrigues Teixeira, Millena; Godinho Zanetti, Danúbia (Revista Gênero e Interdisciplinaridade, 2022)
This paper aims to discuss a theoretical interconnection between the sexual contract and Feminist Psychology, showing up the most possible interventions on practices of clinics with families. Foremost, the theoretical material about the sexual contract was reviewed, by considering Carole Pateman’s literary compositions. Furthermore, it was investigated and presented contributions of the female guidelines by on psychology, defending the theoretical construction and the method of Feminist Psychology. Finally, it was presented reflections about the objectives, bases, and principles of Feminist Family Therapy. This is a fundamental debate, in face of the review of theoretical bases, epistemological and methodological who was the basis of clinical interventions with families. The point of view intensifies, as is follows the articulations between the struggles and achievements of feminist movements, approaching the family therapy closer to more contextualized, critical and socially committed practices, in favor of emancipation and the protagonism of the agents involved with the intervention. The main considerations point to the rupture of a monistic and individualistic view of family interventions. They also indicate new paradigms of welcoming and clinical listening, anchored in the social construction of gender roles and new possibilities for group, family and social interactions.